Menakar Perlindungan Konsumen dari Iklan Menyesatkan dan Produk Ilegal: Studi Kasus Pasta Gigi Marvis - Nursanti Mardiyati (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The development of e-commerce creates consumer protection challenges, particularly from misleading advertisements and illegal products, exemplified by the Marvis toothpaste case lacking a BPOM distribution permit. This study analyzes the implementation gap of the Consumer Protection Law (UUPK) and Health Law in the digital era. The findings show that the circulation of illegal products violates consumer rights (UUPK Art 4) and is subject to severe criminal sanctions (Health Law Art 435). The strategy requires strengthening collective responsibility for businesses (guaranteeing quality and compensation) and influencers (mandatory due diligence and permit verification). Synergistic enforcement (BPOM, Komdigi) and progressive sanctions (including content takedown) are necessary to ensure digital market safety.